BAHASA DAN MODERATISME ISLAM NU: Kajian atas Kata Serapan/Ambilan Arab dalam Buku Bahtsul Matsail - Sukron Kamil (Jurusan Bahasa dan Sastra Arab Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2014)
Language, as Chomsky explains, is the representation of one’s thoughts. It is his/her expressions and psychological responses to the surrounding milieus. Thus, studying religious typology from the perspectives of language is scientifically made possible. This article studies the moderate mainstream of Nahdhatul Ulama (NU), one of Indonesia’s Islamic organizations, from the Arabic words used in Bahtsul Masa’il, the corpus of study series held by elite members of the organization in responding to contemporary issues. There are so many Arabic loan words in the book of Bahtsul Matsail. Most of them are related to aspects of believe and jurisprudence, including terms on rituals for the death. Even though the Arabic words have their corresponding words in Indonesian language, this explains –among which- that Arabic loan words sound more associated to Islamic spirits. Nevertheless, the absence of terms in connotation to political Islam could strongly indicate that the organization, as like Muhammadiyah- does not have any missions to establish Islamic state. Republic of Indonesia with Five Principles of the state, according to NU is final with no need to change it with any other ideology.